Aplicação da tecnologia de grupo em sistemas reais com fluxo complexo: superando barreiras tecnológicas - Petrini, Giuliano (2021)
In the view of the need for a high variety and short life cycle of products, as well as high fluctuation in demand, the search for flexible production systems that, at the same time, present the benefits of mass production systems is imperative. Group technology and cellular manufacturing can contribute to this need. However, the cell formation methods developed in the literature are still abstract, presenting solutions to hypothetical problems that are difficult to reproduce in practice. Practical work is scarce and usually with a low level of complexity and technological restrictions, that is, a small number of products and processes, and machines with functional specificity. This work seeks to develop the PFA (Production Flow Analysis) for cell formation in a real manufacturing environment. With the application of the FFA (Factory Flow Analysis), a step of the aforementioned methodology, the process flow is simplified, making the mathematical (and practical) problem of clustering for cell formation feasible . The work is carried out in a complex environment, with a high diversity of products and processes, and with a large number of machines with functional flexibility and technological restrictions. This study contributes to the cellular manufacturing literature by discussing aspects of a complex manufacturing environment, and presenting proposals for solutions to real constraints, bringing theory and practice close together. As practical implications, this research provides guidelines for solving problems faced by managers when applying group technology / cellular manufacturing.